2024
DOI: 10.1021/acs.nanolett.3c03247
|View full text |Cite
|
Sign up to set email alerts
|

Sensing PEGylated Peptide Conformations Using a Protein Nanopore

Remya Satheesan,
Devika Vikraman,
Parvathy Jayan
et al.

Abstract: Membrane pores are exploited for the stochastic sensing of various analytes, and here, we use electrical recordings to explore the interaction of PEGylated peptides of different sizes with a protein pore, CymA. This wide-diameter natural pore comprises densely filled charged residues, facilitating electrophoretic binding of polyethylene glycol (PEG) tagged with a nonaarginine peptide. The small PEG 200 peptide conjugates produced monodisperse blockages and exhibited voltage-dependent translocation across the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For example, pores showed slightly higher conductance at positive voltages and more frequent gating at negative voltages. Based on this asymmetry in the pore conductance and gating with the direction of the voltage, we presumed the pore orientation, as shown in our previous studies 22,31 (Fig. 1 and S1–S3†).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, pores showed slightly higher conductance at positive voltages and more frequent gating at negative voltages. Based on this asymmetry in the pore conductance and gating with the direction of the voltage, we presumed the pore orientation, as shown in our previous studies 22,31 (Fig. 1 and S1–S3†).…”
Section: Resultsmentioning
confidence: 89%
“…17 Previously, we have shown that cationic CDs and peptides bind to the trans side of the pore with high affinity compared to the cis side, which agrees with the charge distribution in the pore, which allowed us to presume pore orientation. 22,31 Thus, adding CymA to the cis side of the preformed bilayer results in pore insertion with the extracellular side (pore entrance and dense charge pattern) exposed at the trans compartment (Fig. 1a and S1†).…”
Section: Resultsmentioning
confidence: 97%